2012
DOI: 10.1063/1.3682082
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz magnetic field induced coherent spin precession in YFeO3

Abstract: We present the magnetic dipole transition at 0.299 THz excited by magnetic component of terahertz electromagnetic pulse in an antiferromagnetic YFeO3 crystal. The impulsive magnetic field of the terahertz pulse tilts the macroscopic magnetization, causing deviation from the equilibrium position, which is manifested by a sharp absorption at the frequency of the quasiferromagnetic mode of the crystal. The rotating coherent macroscopic magnetization radiates elliptically polarized emission at the frequency of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 27 publications
1
39
0
3
Order By: Relevance
“…By analyzing absorption peaks in the normalized Fourier spectra of the pulses transmitted through the sample, one can obtain information about the spectrum of THz excitations in the sample. The details of the time-domain THz spectroscopy setup can be found elsewhere [22][23][24][25][26][27]. We analyze the THz transmission through the sample in terms of the normalized loss function σ (ω), defined as…”
Section: Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…By analyzing absorption peaks in the normalized Fourier spectra of the pulses transmitted through the sample, one can obtain information about the spectrum of THz excitations in the sample. The details of the time-domain THz spectroscopy setup can be found elsewhere [22][23][24][25][26][27]. We analyze the THz transmission through the sample in terms of the normalized loss function σ (ω), defined as…”
Section: Appendixmentioning
confidence: 99%
“…It has been demonstrated that broadband pulses of THz radiation can serve as a probe of spin resonances in YFeO 3 [22][23][24], ErFeO 3 [25], NdFeO 3 [26], and Tb 3 Ga 5 O 12 [27]. A promising approach to control magnetic order with the help of intense-enough THz pulses has been suggested for NiO [28].…”
Section: Introductionmentioning
confidence: 99%
“…The slower decay of the component polarized along the a axis means that the initially circularly polarized FID signal becomes increasingly elliptical over time, with the long axis of the ellipse oriented along the a axis of the crystal. 26 Extrapolating this trend to long time delays, a nearly linearly polarized THz wave, i.e., a wave radiated by a linearly oscillating dipole (e.g., optical phonon), survives. However, this linearly polarized signal still oscillates at the Larmor frequency, i.e., at the frequency of the precessing magnetic dipole.…”
Section: Data Analysis and Discussionmentioning
confidence: 99%
“…16,17 Recently, the ultrafast THz spectroscopy also proved to be an effective experimental method of detection and manipulation of magnetization in materials utilizing the magnetic field component of the THz transient through magnetic dipole transitions. [18][19][20][21][22] In this fashion, the ultrafast magnetization dynamics in ferromagnetic (FM) 23 and antiferromagnetic (AFM) materials [24][25][26][27] have been investigated.…”
Section: Thz Excitation and Coherent Control Of Spin Resonances Vmentioning
confidence: 99%
See 1 more Smart Citation